Evidence for a proenkephalin-like precursor in amphibian brain. - Kilpatrick, D L (1983)
The mammalian proenkephalin-derived peptides [Leu]enkephalin, [Met]enkephalin, and [Met]enkephalin-Arg6-Phe7 were identified in acid extracts of the brain of Bufo marinus by using reversed-phase HPLC and specific radioimmunoassays. [Met]Enkephalin was the predominant opioid peptide present (270 pmol/g). In contrast, the octapeptide [Met]enkephalin-Arg6-Gly7-Leu8, which is also derived from mammalian proenkephalin, was not detected. The ratio of free [Met]enkephalin to [Met]enkephalin-Arg6-Phe7 was found to be 3.5 to 1, which is similar to that observed in mammalian proenkephalin-containing tissues. Together these data (i) indicate that amphibian brain contains a proenkephalin related to the mammalian precursor and (ii) establish the existence of enkephalins and proenkephalin-derived enkephalin-containing peptides in a submammalian species.